Prostasomes as interlocutor for zygotic epigenome health: role of prostasome secretome in maintenance of zygotic epigenome.: Prostasomes in zygotic epigenome health - RAJHANS, RAJIB; Kumar, Amit (Indian Journal of Dairy Science, 2023)
Prostasomes as transgenerational epigenetic toolbox has not been established, its role in transferring small RNA, lncRNA as paternal messages is yet to be explored. The present study was undertaken to establish role of prostasomes in modulating testicular and vaginal environmental cues such as protein and RNA messages through to zygote and thereby acting as interlocutor of paternal genome. The results from the study found out prostasomes fusion with spermatozoa takes place at the time of maturation and capacitation wherein it causes downregulation of ROS (Protein and mRNA) in terms of decreased NADPH and NOS activity significantly (p